The impact of demographic problems on human resource development ("Journal "U". Economy. Management. Finance.", 2024)
This article examines the impact of demographic problems on the development of human resources. Demographic problems such as low birth rates, high mortality, population ageing and migration can have a serious impact on human resource development in various countries. The article analyzes various strategies and measures aimed at solving demographic problems and improving the efficiency of human resources.
Keywords: Demography; human resource; demographic trends; migration; population aging; fertility; demographic imbalance; state of the economy; economic growth; state policy